Efficacy of activated sludge in removing Cryptosporidium parvum oocysts from sewage. - Villacorta-Martinez de Maturana, I (1992)
Primary clarifier effluent (procedure B) and final effluent (procedure A) from a wastewater treatment plant were enriched with Cryptosporidium parvum oocysts obtained from the feces of naturally infected calves. Procedure B samples alone were subjected to a laboratory simulation of activated-sludge treatment. Coccidium-free neonatal CD-1 mice were then inoculated intragastrically with procedure A or procedure B samples. Seven days after inoculation, the intensity of oocyst infection in procedure B mice was 91% less than in procedure A mice (controls).